Forecasting the monthly discharge of the Mekong River - Twu, Chung-tung; Huynh, Ngoc Phien; Kanchit Malaivongs; Le Huu Ti; The Government of Germany, Carl Duisberg-Gesellschaft e. V. (CDG) (Bangkok : Asian Institute of Technology, 1983)
In this study, three different statistical methods are applied to forecast the monthly discharge of the MEKONG RIVER at five stations using only the discharge data. The Box-Jenkins model was used directly to forecast the monthly discharge using its own time series. Moreover, the Multiple Regression (MRG) and the Group Method of Data Handling (GMDH) are also employed to forecast the monthly discharge using additional information, such as the maximum and minimum daily values and the discharges of the last day in previous months. The results obtained show that all the three methods perform satisfactorily in providing forecasts with leas time equal to one month. The Box-Jenkins and Multiple Regression Analysis can be used to provide forecasts with long lead time, even though less accurate results are observed.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1983
Keywords: Stream measurements -- Mekong River